ICT4D Research in Developing Countries: A Call for Pragmatism Approach - Gabriel Ndung'u Kamau (Institut Teknologi Bisnis AAS Indonesia, 2022)
Today, Information Systems research and in particular in the area of ICT4D in developing nations is dominated by positivism and interpretivism paradigms. Information systems contributions are influenced by historical, cultural, and political contexts in which it is done. Researchers in this area question the appropriateness of positivism and interpretivism philosophical foundations to conduct ICT4D research. This paper explores the use of pragmatism as an alternative research paradigm to that can be employed to understand the state of the ICT4D research. Research drawing explicitly on pragmatism is still relatively rare. The paper reviews the pragmatism in terms of its ontology, epistemology, axiology and methodology and its value in the ICT4D research discipline. As a new paradigm, pragmatism disrupts the assumptions of older approaches based on the philosophy of knowledge, while providing promising new directions for conducting and understanding the nature of research in the area of ICT4D in developing countries. It is anticipated the readers of the article to make a more informed choice for themselves on whether or not to pursue the path ofpragmatism their own research. KeywordAxiology, epistemology, ICT4D, methodology, ontology, pragmatism, research paradigms